For this case we have the following system of equations:
![y-15 = 3x\\-2x + 5y = -3](https://img.qammunity.org/2020/formulas/mathematics/high-school/wyeuda8nhyeysgz89p3qhtcjv6g4zwwgoe.png)
We multiply the first equation by -5:
![-5y + 75 = -15x](https://img.qammunity.org/2020/formulas/mathematics/high-school/z869jqs83zeoz7m0eia1zjdejbc5fyytcp.png)
Now we add the equations:
![-2x-5y + 5y + 75 = -3-15x\\-2x + 75 = -3-15x\\-2x + 15x = -75-3\\13x = -78\\x = \frac {-78} {13}\\x = -6](https://img.qammunity.org/2020/formulas/mathematics/high-school/cn5o2wkj6jqu62p7ix0so3kvse39zt90ve.png)
We find the value of the variable "y" according to the first equation:
![y = 3x + 15\\y = 3 (-6) +15\\y = -18 + 15\\y = -3](https://img.qammunity.org/2020/formulas/mathematics/high-school/hfm2vka92xipsh4248egb5yd9b3l1lhy3z.png)
The solution of the system is: (-6, -3)
Answer:
(-6, -3)
Option C